Kelebihan pengetahuan kejayaan pasaran dari kaca mata 14 tokoh wawasan - Ruggles, Rudy L. 1966-; Holtshouse, Dan; Phoay, Hong Sim (Institut Terjemahan Negara Malaysia Berhad, 2007)
A selection of knowledge gurus tackle various aspects of this vital resource in the economy. Topics covered include: turning knowledge into products; the dynamics of knowledge creation; building knowledge into strategy; and profiting from the economics of knowledge.